Concrete Quality Analysis Based on Compressive and Splitting Tensile Strength Using Inferential Statistical Methods - Muhammad Alifsyah Ananda Rudyta; Eswan Eswan; Wahyu Mahendra (Journal of Applied Sciences, Management and Engineering Technology, 2026)
This research aims to analyze the effect of using two types of coarse aggregates, Senoni and Palu, combined with silica sand as a fine aggregate replacement, on the compressive strength and split tensile strength of concrete. Tests were conducted at concrete ages of 7, 14, 21, and 28 days to observe the development of concrete strength over time. A total of 80 cylindrical specimens were prepared, consisting of 40 specimens using Senoni aggregate and 40 specimens using Palu aggregate, each tested for both compressive and split tensile strength.Statistical analysis using the independent sample T-test was applied to determine the differences in strength between the two types of aggregates. The results showed that there were significant differences in compressive strength at all testing ages, indicated by significance values (Sig.) 0.05 and t-calculated values greater than t-table, leading to the rejection of H₀ and the acceptance of H₁. This confirms that the physical characteristics of the aggregates have a significant effect on the compressive strength of concrete. In contrast, for split tensile strength, not all ages showed significant differences. Some ages produced Sig. values 0.05, indicating no statistically significant differences between the two aggregates under those conditions.Furthermore, a statistical correlation analysis between compressive strength and split tensile strength was conducted. The results indicated a moderately strong and positive relationship between these two parameters, although the strength of the correlation varied depending on the concrete age. Overall, this study confirms that the selection of coarse aggregate types plays an important role in concrete performance, both in resisting compressive loads and indirect tensile forces.